TIPOLOGI KELUARGA PADA KELUARGA MISKIN DAN TIDAK MISKIN - Ginanjarsari, Gina; Sunarti, Euis (Jurnal Ilmu Keluarga dan Konsumen, 2013)
Family typology is a concept that describes the behavior of family in facing stressful conditions. Family typology consists of 4 dimensions such as regenerative families, resilient families, rhythmic families, and ritualistic families. This research was to analyze the differences of family typology between poor and non-poor family. Families in this study consisted of 30 poor families and 30 non-poor families which were selected by stratified random sampling. Dimensions of family typology was measured by eight family typology indicator, that are family hardiness, family coherence, family bonding, family flexibility, family times and routines, the valuing family times and routines, family tradition, and family celebration. The results showed that resilient family typologies in poor families different significantly from non-poor families, where non-poor families have higher percentage for the typology of resilient family.